Sistem Informasi Pemasaran Berbasis Web Studi Pada Rainbow Tour and Transport - Restyafani, Fais; Winarto (Journal Of Accounting and Business, 2025)
This study examines the design of a web-based marketing information system for Rainbow Tour and Transport, a travel agency based in Surabaya. The increasing use of the internet in Indonesia presents a significant opportunity for businesses to expand their reach and improve service efficiency through digital platforms. This research aims to address limitations in the current promotional methods, which rely primarily on social media, by developing a comprehensive website to enhance accessibility, provide detailed information, and facilitate customer interactions. Using a descriptive qualitative approach and the prototype system development method, this study designed and implemented a user-friendly website. Key features include service and tour package details, an interactive interface, and a contact section for easy communication. The results indicate that the web-based system significantly improves information dissemination and streamlines the booking process, promoting better customer engagement and operational efficiency. This study highlights the importance of integrating technology into traditional marketing practices for business growth in the digital era.